POLA SEBARAN BATUBARA FORMASI NANGGULAN KABUPATEN KULONPROGO DAERAH ISTIMEWA YOGYAKARTA - Heriyadi, Nur Nur Widi Astanto Agus Tri; Tania, Dina (Jurnal Teknologi Technoscientia, 2018)
Coal is one of the energy resources still become the primary needs of strategic energy for sustaining national energy in Indonesia. This study discusses coal existence in Nanggulan Formation at Yogyakarta area. Coal distribution pattern in Nanggulan Formation can provide the geometry conception base on the geological research in Watupuru area encountered three coal outcrop (OC_1, OC_2, and OC_3) stratigraphically is at the bottom layer.Coal distribution in the research area influenced by the pattern of anticline structure which has the position of the wing of East and West with the relative anticline axis of north-south direction. Reconstruction results show there is two-seam of coal, for the first seam layer have 0,55 meters thickness and for the second seam layer have 20,57 meters thickness. Seam 1 of reconstructed surface data has spread on the East side of the anticline. Seam 2 stratigraphically under seam 1 of the reconstruction results indicate that the spread is close to the anticline axis and spreads on the east side of the anticline with a 26o slope and the western wing side of the anticline with a slope 10o.